2020
DOI: 10.26803/ijlter.19.8.13
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Online Learning during the Covid-19 Pandemic on Madura Island, Indonesia

Abstract: This study aimed to determine the online learning process and the associated obstacles experienced by students. With the background of the ongoing Covid-19 pandemic outbreak, this study sought to uncover what social constructions the students engage in related to the new policy for online learning that has recently been enforced by the Indonesian government. A quantitative study was conducted with a descriptive research approach. There were 274 college student respondents from Madura, Indonesia. This study fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
1
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 59 publications
6
126
1
22
Order By: Relevance
“…Kruse and Veblen (2012) revealed that the utilization of YouTube for digital learning brings in opportunities for educators to increase the intensity of uploading videos. This supports a participatory culture in terms of making circulatory videos, images and allowing for user expressions (Febrianto et al, 2020). The result presented in Table 2 and Figure 2 showed that lecture is the most used method for emergency online learning in Assam with a student response rate of 100% followed by sharing PDF/Word files as supplementary study material (83.33% response), giving assignment (68.18% response).…”
Section: Implementation Mechanism Of Emergency Online Learning Duringsupporting
confidence: 57%
See 1 more Smart Citation
“…Kruse and Veblen (2012) revealed that the utilization of YouTube for digital learning brings in opportunities for educators to increase the intensity of uploading videos. This supports a participatory culture in terms of making circulatory videos, images and allowing for user expressions (Febrianto et al, 2020). The result presented in Table 2 and Figure 2 showed that lecture is the most used method for emergency online learning in Assam with a student response rate of 100% followed by sharing PDF/Word files as supplementary study material (83.33% response), giving assignment (68.18% response).…”
Section: Implementation Mechanism Of Emergency Online Learning Duringsupporting
confidence: 57%
“…Kruse and Veblen (2012) revealed that the utilization of YouTube for digital learning brings in opportunities for educators to increase the intensity of uploading videos. This supports a participatory culture in terms of making circulatory videos, images and allowing for user expressions (Febrianto et al, 2020).…”
Section: Resultsmentioning
confidence: 69%
“…With the outbreak of COVID-19 around the globe, many countries, including Jordan, have shifted education from on-campus face-to-face to online education. This sudden change in the learning/teaching process has garnered positive and negative attitudes from both university students and instructors (Agung, Surtikanti & Quinones, 2020;Febrianto, Mas'udah, & Megasari, 2020). This study therefore explores Jordanian students' attitudes toward online learning in light of the following variables: gender, level of seniority, availability of technological devices, socioeconomic status, and training and orientation for using eLearning platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Online learning during the COVID-19 pandemic and lockdowns has received much attention in literature on synchronous and asynchronous computermediated communication (Agung et al, 2020;Febrianto et al, 2020). In fact, even prior to the worldwide spread of COVID-19, many studies have proved the pedagogical benefits of computer-assisted language learning (CALL), such as decreasing learner anxiety and providing shy learners with a safe learning environment (Beauvois & Eledge, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The use of various media sources, one of which is courageous learning media [45], is expected to help students understand lecture material. Moreover, the condition of the Covid-19 pandemic in all campuses must learn with new methods [46] [47], including students and lecturers who must learn bravely [48]. The ability of lecturers to use bold learning media during this pandemic [49] is expected to increase students' interest in learning and become a benchmark or success in brave learning [50][51].…”
Section: Introductionmentioning
confidence: 99%